Does wearing arthritis gloves help with hand pain and function? A qualitative study into patients' views and experiences. Issue 1 (12th February 2022) - Prior, Yeliz; Bartley, Carol; Adams, Jo; Firth, Jill; Culley, June; O'Neill, Terence W; Hammond, Alison
Abstract: Objective: Arthritis gloves are frequently prescribed to people with undifferentiated inflammatory arthritis (UIA) or RA to help reduce hand pain and improve function. Nested within a randomized controlled trial testing the effectiveness of arthritis gloves (Isotoner gloves vs loose-fitting placebo gloves) in people with RA and UIA, this qualitative study aimed to explore participants' views on the impact of wearing arthritis gloves on their hand pain and function. Methods: Semi-structured one-to-one interviews were conducted with purposively selected participants following 12 weeks of glove wearing. Participants and the interviewer were blinded to the treatment allocation. Interviews were audio-recorded, transcribed verbatim and analysed using thematic analysis. Results: Participants (intervention: n = 10; control: n = 9) recruited from 13 National Health Service hospital sites in the UK participated in the interviews. Two main themes, with sub-themes, were elicited from the data: mechanisms determining glove use: 'As soon as your joints get a bit warmer, the pain actually eases' (thermal qualities; glove use in daily activities; glove use during sleep); and ambivalence about benefits of arthritis gloves: 'I suppose a normal pair of gloves would do the same sort of thing?' (are they a help or hindrance?; aesthetic appeal; future use of gloves). Conclusion: Participants had ambivalent views on the impact of both the intervention and the loose-fitting placebo gloves on their hand pain and function, identifying warmth as the main benefit. Ordinary mid-finger-length gloves widely accessible from high street suppliers could deliver warmth and provide the perceived benefits to hand pain and function. Trial registration: ISRCTN, ISRCTN25892131; registered 5 September 2016 : retrospectively registered.